Evaluasi Teknologi Informasi menggunakan COBIT 5 Fokus Proses DSS02, DSS03, dan DSS04 (Studi Kasus: PT. Garam (Persero)) - Melisa Widya Astuti; Suprapto Suprapto; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT. Garam (Persero) is a company that operates as a production agent for the construction of Salt and is approved by the National Salt in Indonesia, and is always working to realize food in the salt field. So, to help the business process activities carried out by PT. Garam (Persero) applies ERP system services. In implementing ERP system services, there are obstacles such as incidents and problems that affect PT. Garam (Persero). With the constraints that occur it is necessary to evaluate information technology using the COBIT 5 framework for this research and the chosen DSS (Delivery, Service and Support) subdomain focus is DSS02: Manage Service Requests and Incidents, DSS03: Manage Problems and DSS04: Manage Continuity. The study was conducted aiming to determine the current capability level and GAP. The results showed the capability level obtained from the subdomain process DSS02, DSS03, and DSS04 was 1 and in all subdomain processes the GAP value was 1. In order for the company to reach the desired target level, recommendations were given for completing the documentation of the work product output document, making procedures more detailed and detailed information regarding handling requests and problem incidents.